2017
DOI: 10.1371/journal.pone.0185689
|View full text |Cite
|
Sign up to set email alerts
|

Zika beyond the Americas: Travelers as sentinels of Zika virus transmission. A GeoSentinel analysis, 2012 to 2016.

Abstract: BackgroundZika virus (ZIKV) was first isolated in Africa; decades later, caused large outbreaks in the Pacific, and is considered endemic in Asia. We aim to describe ZIKV disease epidemiology outside the Americas, the importance of travelers as sentinels of disease transmission, and discrepancies in travel advisories from major international health organizations.Methods and findingsThis descriptive analysis using GeoSentinel Surveillance Network records involves sixty-four travel and tropical medicine clinics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 35 publications
0
25
0
1
Order By: Relevance
“…These travelers essentially act as sentinels of emerging epidemics when a source country does not have the capacity to detect these infections in a timely manner. Such networks have detected a sarcocystis outbreak in Malaysia [100], dengue virus outbreaks in Angola [101], and tracked the spread of Zika virus globally [102]. With improved surveillance and early warning systems, and by harnessing travelers as sentinels, it is possible to piece together a global picture of emerging and re-emerging infectious diseases.…”
Section: Public Health Implications Of Infections Transmitted Via Airmentioning
confidence: 99%
“…These travelers essentially act as sentinels of emerging epidemics when a source country does not have the capacity to detect these infections in a timely manner. Such networks have detected a sarcocystis outbreak in Malaysia [100], dengue virus outbreaks in Angola [101], and tracked the spread of Zika virus globally [102]. With improved surveillance and early warning systems, and by harnessing travelers as sentinels, it is possible to piece together a global picture of emerging and re-emerging infectious diseases.…”
Section: Public Health Implications Of Infections Transmitted Via Airmentioning
confidence: 99%
“…The detection of ZIKV-RNA on BFP collected by a symptomatic traveller to Haiti in EW 39 ( Figure 1E), confirmed ongoing transmission of ZIKV beyond EW 33, when Haiti sent its last update to PAHO (Pan American Health Organization, 2017;Journel et al, 2017). This finding highlights the role of travellers as sentinels for ZIKV circulation (Leder et al, 2017). It also illustrates the utility of BFP, which allowed us to obtain a molecular diagnosis of ZIKV in three cases.…”
Section: Discussionmentioning
confidence: 54%
“…1B). To further confirm the timing of a Zika outbreak in Cuba, we obtained travel-related infection data from the GeoSentinel Surveillance Network (Hamer et al, 2017;Leder et al, 2017) and found that 76% of the Zika cases associated with travel from Cuba were diagnosed in 2017 (22 of 29; Fig. 1C).…”
Section: Uncovering An Unreported Zika Outbreak In Cubamentioning
confidence: 99%
“…Infectious disease surveillance of international travelers has long been an effective method to detect pathogens circulating in resource-limited areas (Hamer et al, 2017;Harvey et al, 2013;Leder et al, 2013Leder et al, , 2017Wilder-Smith et al, 2012). We hypothesized that similar frameworks could be leveraged to improve Zika virus surveillance, as many regions in the Americas affected by the epidemic attract large volumes of international visitors from countries with stronger healthcare and surveillance systems (Wilder-Smith et al, 2018).…”
Section: Introductionmentioning
confidence: 99%